Christianity and Judaism in the life of Obadiah, the Norman proselyte, through the prophecy of Joel - García de la Calle, Sylvie Denise ('Ilu. Revista de Ciencias de las Religiones, 2012)
In the Cairo Genizah were manuscripts with Gregorian notation and Hebrew script. They also appeared documents that point to author of the scores at Giovanni-Obadiah, a twelfth century Christian monk, born in southern Italy, who converted to Judaism. Until now, the study of this personage has been realized almost exclusively from the Jewish point of view. Nevertheless, like Obadiah synthesizes the traditions Christian and Jewish in its notation when copying Hebrew melodies with Christian notation, also it does in his texts. Obadiah transcribed a Latin appointment of Joel to Hebrew characters. This article pretends to oppose his conversion to Judaism with his ordination as a Christian monk through the prophecy of Joel, which implies an intense dialogue between the two traditions.
Keywords: Jewish Music; Cairo Genizah; Messianism; Jewish holidays; Pentecost; Norman proselyte.